KADAR HEMOGLOBIN PADA SISWI PONDOK PESANTREN PUTRI KECAMATAN MRANGGEN KABUPATEN DEMAK JAWA TENGAH - Rahayu Astuti; Ali Rosidi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Anemia is a nutritional problem in Indonesia. Prevalence of anemia in adolescents still high,whereas in adolescents living in boarding schools showed a higher prevalence. The purpose ofthe study analyzed the differences of levels of hemoglobin (Hb) based on student characteristics,menarche status and body mass index (BMI). This study is an analytic with cross-sectionaldesign. Population were all female students from two boarding schools (pesantren) who was inMranggen the District of Demak. The entire student also attending formal education inMadrasah Tsanawiyah. Sampling with the inclusion and exclusion criteria. The variablesstudied were hemoglobin levels were measured by Cyamethemoglobin, student identity dataincluding age, class, medical history, number of children, father education and menarche status,and body mass index (BMI). Statistical analysis used univariate and bivariate analysis of theMann Whitney test and Kruskal Wallis test. Data normality test used Kolmogorov Smirnov test.The level of significance was 5%. The results showed that of 213 girls studied, who suffer fromanemia 159 people (74,6%). Lowest hemoglobin level of 7,56 g/dL, the highest 14,80 g/dL, anaverage of 11,15 g/dL and standard deviation 1,46 g/dL. There is a significant difference (p =0,000 and p = 0,007) mean Hb level by grade and age. There were no differences in mean Hblevels by categories of children, father education, menarche status, and BMI categories (p>0,05). Keywords: hemoglobin levels, anemia, menarche status, BMI, boarding school